Consumer choice of on-demand mHealth app services: Context and contents values using structural equation modeling. (January 2017) - Lee, Euehun; Han, Semi; Jo, Sang Hyun
Highlights: Users of mHealth application service tend to try the mHealth app services to satisfy their curiosity rather than for managing their health. The current mHealth application services do not provide practical functions for users to manage their health in that they think they are not reassured by the services. Users of mHealth application services think that the services are useful and convenient for seeking health information and recording the condition of their health such as weight, diet, etc. Abstract: Objective: As smartphone penetration increases and the technology advances, various mobile services have reached the market. mHealth Applications are specifically highlighted for phenomena such as global aging & well-being, but the technology-driven mHealth services have not been successful in the market because consumer needs have not been reflected in the services properly. This study developed a research model consisting of context/contents values to explain the intention of consumers over the age of 40 in using mHealth Applications. Method: To carry out this research, an online survey was conducted of mHealth Application users and recognizers in South Korea who are over 40 years old. 313 respondents gave usable data; those data were analyzed via a structural equation model. Results: Context values (health stress, epistemic) produce an effect on contents values and contents values (convenience, usefulness), excepting reassurance and enjoyment, positively affect the intention to use mHealth Applications. The findings indicate that people who are stressed out about their health and are interested in new ways to control their health think that mHealth Applications are very convenient and useful because people can manage their health at home or at the office, even when they cannot go to a hospital. However, they feel that the current level of service does not provide reassurance. The level of service is behind people's expectations. Hence, a market-oriented approach that can determine user needs, specifically in terms of the reassurance value in the mHealth service field, is needed to develop mHealth Applications.